Integration of POAC Management Based on Progressive Islamic Values in Strengthening Student Character: A Case Study at Senior High School - Keissa Melian; Eva Emania Eliasa (Early Publishing, 2026)
This study aims to analyze the implementation of the management function of Planning, Organizing, Actuating, and Controlling (POAC) in the management of the Muhammadiyah Student Association (IPM) program and its contribution to strengthening the character of progressive Islamic values-based students at SMA Muhammadiyah Yogyakarta. Research on religious-based student organizations has tended to focus on ideological regeneration and religious activities, while studies that integrate modern management functions with the formation of student character are still relatively limited. This study uses a qualitative approach with a case study design. The research informants amounted to nine people consisting of the principal, vice principal for student affairs, HDI coaches, administrators, and members of the HDI who were selected purposively. Data collection was carried out through participatory observation, in-depth interviews, and documentation. Data analysis uses the interactive model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, and conclusion drawing with validity tests through source triangulation, technique triangulation, and member checking. The results of the study show that HDI management has implemented the POAC management function systematically through participatory planning, formal organizational structures, implementation of value-based programs, and continuous reflective evaluation. The findings of the research resulted in a values-based student organizational management model that integrates modern management principles with progressive Islamic values in strengthening the humanist character of students. Theoretically, this research contributes to the development of the concept of value-based educational management, especially in the management of religious-based student organizations. Practically, this study provides a reference for schools in managing student organizations as a medium for fostering leadership and character.